Assessing the Role of Electives Module in Shaping Career Choices of Medical Undergraduate Students - Devi , G Durga; R, Rahe; Puhazhendhi, T; Devaki, PR; Koshy , Jinu Merlin; R, Archana (Bangladesh Journal of Medical Science, 2025)
Background The introduction of elective postings in 2020 as part of the competency-based medical education (CBME) framework marked a significant advancement in the medical curriculum for undergraduate students. These electives provide crucial handson experience across various specialties, allowing students to tailor their education according to their interests. Objective: This study aims to assess the impact of the elective module on the career choices of medical undergraduate students. Methods A cross-sectional study was conducted at Sree Balaji Medical College and Hospital, Chennai, involving MBBS students from the 2019-2020 and 2020-2021 batches. A total of 298 students participated, providing informed consent. A pretested questionnaire with open and closed-ended questions was administered, focusing on students’ elective choices, perceptions, and career interests. The “Electives Perception Indicator” (EPI) was measured using a 5-point Likert scale. Results The majority of students reported positive experiences in both Block I and Block II electives. Feedback indicated high satisfaction with faculty guidance and patient interactions. Approximately 29.9% of students strongly believed that elective postings should be mandatory, and a significant increase in clarity regarding career choices was observed post-elective. Despite some concerns about workload and the relevance of content, students recognized the value of electives in enhancing their clinical skills and confidence in specialty selection. Conclusion Elective postings are viewed as a valuable component of the medical curriculum, significantly influencing students’ career decisions. Proactive engagement from students is essential to maximize these opportunities. Continued evaluation and adaptation of the elective program are recommended to better align with student needs and aspirations. BJMS, Volume: 24. Supplementary Issue 2025, Page : 149-155